Analyzing parliamentary discourse: systemic functional perspective - Treimane, Laura (Kalbotyra, 2011)
Contemporary research views parliamentary discourse as a variety of political language which is largely defined by its contextual properties and thus requires a contextual approach of analysis. According to the systemic functional theory, a contextual discourse analysis is the analysis of register, i.e. the analysis of the text as embedded in its situational context. The present research demonstrates the relevance of the systemic parameters to parliamentary discourse analysis where the parliamentary transcripts of the debate held at the British House of Commons and the Latvian Parliament (Saeima) are used as the empirical data. The investigation of parliamentary texts reveals a consistent occurrence of fixed lexico-grammatical patterns, namely, noun phrases which are realized as politeness formulas and verb phrases which ensure the legislative procedure. Both in Latvia and in Britain these fixed patterns may be considered as indexical features of parliamentary register. The contextual analysis reveals significant discrepancies in the interpretation of the categories of context within systemic functional linguistics and underscores the necessity of developing a more systemic context framework which would employ extralinguistic, rather than linguistic, criteria for context analysis.